Enhancing elementary students learning motivation through assemblr edu-based augmented reality media on ecosystem topic - Ismatun Nisak; Aan Widiyono (Lentera Negeri, 2026)
Student difficulties in understanding the Natural and Social Sciences (IPAS) subject are caused by the conceptual essence of the content and the restricted utilization of engaging educational resources. This research seeks to create and evaluate the validity, feasibility, and efficacy of Augmented Reality (AR) media through the Assemblr Edu application concerning ecosystem content. This research utilized a Research and Development (R&D) approach using the ADDIE model, comprising the phases of analysis, design, development, implementation, and evaluation. The study participants included 1 teacher and 20 third-grade pupils from SDN 1 Mulyoharjo, comprising 10 female and 10 male students. The implementation of the study was conducted over three meetings. Data gathering methods were conducted using observation, interviews, and surveys. The instrument for measuring learning motivation was validated and assessed for reliability before its use, and it was found to be both valid and reliable. The results showed that the media validity score was 86% (valid category), while the material validity score was 89.3% (valid category). Student feedback regarding media usage received a percentage of 91.1% (excellent category). Additionally, the outcomes of the paired sample T-test revealed a significance value of 0.000 < 0.05, and the N-Gain value was 0.3611 (moderate category, lower threshold), signifying a moderate enhancement in student learning motivation. Consequently, the use of Augmented Reality media through the Assemblr Edu app is deemed practical and fairly efficient in enhancing ecosystem education.